ANALISIS RENCANA PENGGUNAAN RADAR MONITOR SEBAGAI ALAT PENUNJANG SARANA PENGAWASAN (SURVEILLANCE) DI UNIT FLIGHT SERVICE STATION (FSS) PERUM LPPNPI CABANG MANADO - Mohammad Alifi Widoanggoro; Ade Irfansyah; Paramita Dwi Nastiti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Perum LPPNPI Manado Branch, as a provider of flight navigation services, continues to make efforts to improve flight navigation services provided in accordance with the International Civil Aviation Organization (ICAO) Doc 4444 Chapter 8 Radar Services which explains the use of radar in flight information services. The problem faced by Aeronautical Communication Officer (ACO) personnel is that there is no use of radar monitors as a support for monitoring facilities at the Manado Flight Service Station (FSS) unit. This resulted in the lack of maximum surveillance services provided by Aeronautical Communication Officer (ACO) personnel in conducting traffic scouting and knowing the aircraft's position accurately in the Manado Flight Service Station (FSS) airspace. The purpose of this study is to study the importance of using a radar monitor in the Flight Service Station (FSS) control room as a means of supporting aircraft movement surveillance. In this study, the authors used quantitative methods and distributed questionnaires to 8 Aeronautical Communication Officer (ACO) personnel as respondents. The results of this study are expected to provide an alternative solution to the problem for Perum LPPNPI Manado Branch, namely by adding a radar monitor facility in the Flight Service Station (FSS) control room in order to increase the flight navigation services provided